The Timed Up and Go dual-task test’s cognitive and motor outcomes show promising test-retest reliability in older adults with perceived memory impairment - Löfgren, Niklas; Giedraitis, Vilmantas; Halvorsen, Kjartan; Rosendahl, Erik; Åberg, Anna Cristina (Frontiers in Aging, 2026)
BackgroundIt is of utmost importance to identify older adults at risk of cognitive impairment at the earliest possible stage. Previous research supports the potential of investigating step parameters and turn duration during Timed Up and Go (TUG) during single and dual-task (TUGdt) conditions to detect subtle impairment. The aim of this study was therefore to investigate the test-retest reliability and measurement error of novel outcomes related to TUG and two TUGdt tests, TUGdt-NA (naming animals) and TUGdt-MB (reciting months in reverse order), in older adults with perceived memory impairment.MethodsThirty-four participants (18 women, mean age 76) were included and assessed with TUG, TUGdt-NA and TUGdt-MB on two different occasions, 5–10 days apart. Tests were video recorded for data extraction of spatiotemporal step parameters and turn duration. Reliability of motor and cognitive outcomes were analyzed with intraclass correlations (ICC2.1), standard errors of measurement and minimal detectable change (MDC). The proportional measurement error was presented with MDC%.ResultsThe results showed very good reliability (ICC2.1 ≥ 0.85) regarding total completion times, although the measurement error and proportional measurement error (MDC%) was higher during TUGdt conditions than TUG. The reliability of cognitive outcomes during TUGdt favored TUGdt-MB (ICC2.1 ≥ 0.77, MDC% ≤39.8). Step length was the step parameter with highest reliability (ICC2.1 ≥ 0.86) and lowest proportional measurement error (MDC% ≤21.4) across conditions, whereas turn duration showed good reliability during TUG and TUGdt-MB (ICC2.1 ≥ 0.74, MDC%≤38.9).ConclusionThe results support the potential of including TUG and TUGdt outcomes in cognitive risk evaluations among older adults.Trial Registration NumberUppsala-Dalarna Dementia and Gait Project | ClinicalTrials.gov, identifier NCT05893524.